1982
DOI: 10.1128/mcb.2.10.1270
|View full text |Cite
|
Sign up to set email alerts
|

Actin from Saccharomyces cerevisiae.

Abstract: Inhibition of DNase I activity has been used as an assay to purify actin from Saccharomyces cerevisiae (yeast actin). The final fraction, obtained after a 300-fold purification, is approximately 97% pure as judged by sodium dodecyl sulfate-gel electrophoresis. Like rabbit skeletal muscle actin, yeast actin has a molecular weight of about 43,000, forms 7-nm-diameter filaments when polymerization is induced by KCl or Mg2+, and can be decorated with a proteolytic fragment of muscle myosin (heavy meromyosin). Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 42 publications
2
46
1
Order By: Relevance
“…As reported earlier, this behaviour is restricted to non-muslce actins [40], with yeast actin showing the most dramatic difference compared to muscle actin [41]. Greer and Schekman [42] showed that yeast actin tends to aggregate in the presence of Ca2+, and observations of the Ca2 + influence on the polymerization of bovine p-actin implicate the presence of an additional, lowaffinity Ca2+-binding site on p-actin compared to a-actin [43].…”
Section: Resultsmentioning
confidence: 76%
“…As reported earlier, this behaviour is restricted to non-muslce actins [40], with yeast actin showing the most dramatic difference compared to muscle actin [41]. Greer and Schekman [42] showed that yeast actin tends to aggregate in the presence of Ca2+, and observations of the Ca2 + influence on the polymerization of bovine p-actin implicate the presence of an additional, lowaffinity Ca2+-binding site on p-actin compared to a-actin [43].…”
Section: Resultsmentioning
confidence: 76%
“…Profilin and myosin II of D. discoideum show different affinities for actin from various sources (Greer and Schekman, 1982;Haugwitz et al, 1991), but Dd plastin is the first protein known from this organism that does not bind actin from rabbit skeletal muscle to any significant extent. The protein appears therefore to bind to a region where the major actin (actin 15) of D. discoideum (Vandekerckhove and Weber, 1980) differs in its structure from rabbit a-actin.…”
Section: Distribution Of Dd Plastin In Cells Of Different Developmentmentioning
confidence: 99%
“…It contains a single essential actin gene (ACT1), and easy genetic manipulation allows the ready exchange of a mutant actin gene for its wild-type counterpart. Its actin is about 90% identical in amino acid sequence to the mammalian cytoskeletal actins and about 87% identical to the striated muscle actins [Greer and Schekman, 1982;Ng et al, 1985]. Its actin cytoskeleton contains many of the same proteins as do mammalian cells, and robust methods have been established for assessing in vivo cytoskeleton function in yeast using a combination of genetics and microscopy.…”
Section: Budding Yeast As An Expression System For Mutant Actinsmentioning
confidence: 99%